Involvement of Organic Cation Transporter-3 and Plasma Membrane Monoamine Transporter in Serotonin Uptake in Human Brain Vascular Smooth Muscle Cells - Li, Rachel W.; Yang, Cui; Kwan, Yiu-Wa; Chan, Shun-Wan; Lee, Simon M.; Leung, George P. (Frontiers in Pharmacology, 2013)
The serotonin (5-HT) uptake system is supposed to play a crucial part in vascular functions by “fine-tuning” the local concentration of 5-HT in the vicinity of 5-HT2 receptors in vascular smooth muscle cells. In this study, the mechanism of 5-HT uptake in human brain vascular smooth muscle cells (HBVSMCs) was investigated. [3H]5-HT uptake in HBVSMCs was Na+-independent. Kinetic analyses of [3H]5-HT uptake in HBVSMCs revealed a Km of 50.36 ± 10.2 mM and a Vmax of 1033.61 ± 98.86 pmol/mg protein/min. The specific serotonin re-uptake transporter (SERT) inhibitor citalopram, the specific norepinephrine transporter (NET) inhibitor despiramine and the dopamine transporter (DAT) inhibitor GBR12935 inhibited 5-HT uptake in HBVSMCs with IC50 values of 97.03 ± 40.10 M, 10.49 ± 5.98 M and 2.80 ± 1.04 M, respectively. These IC50 values were 100-fold higher than data reported by other authors, suggesting that those inhibitors were not blocking their corresponding transporters. RT-PCR results demonstrated the presence of mRNA for organic cation transporter (OCT)-3 and plasma membrane monoamine transporter (PMAT), but the absence of OCT-1, OCT-2, SERT, NET and DAT. siRNA knockdown of OCT-3 and PMAT specifically attenuated 5-HT uptake in HBVSMCs. It is concluded that 5-HT uptake in HBVSMCs was mediated predominantly by a low-affinity and Na+-independent mechanism. The most probable candidates are OCT-3 and PMAT, but not the SERT.